The Prediction of Shift Work Tolerance by means of Morning-type, Rigidity Sleeping Habits and Big Five Factors of Personality - A . Mohammadzade Ebrahimi (Salāmat-i kār-i Īrān, 2013)
Background and Aim : The aim of the present study was to examine the personality variables of morning-type, rigidity, neuroticism , extroversion, openness, agreeableness and conscientiousness as predictors of shift work tolerance in an industrial company in Ahvaz.   Methods: The sample consisted of 245 shift workers which were selected by the use of stratified random sampling. At first the participants divided into two groups (low tolerance shift workers versus high tolerance shift workers) by using Survey of Shift workers. Then each group of participant s was evaluated by using NEO questionnaire. In order to analyze the data, the discriminate analysis and in the validation stage, the Pearson's Correlation Coefficient were applied.   Results: Findings, confirm the hypothesis of this study. On the other hand, findings revealed that tolerance of shift work can be predicted from Personality variables.   Conclusions: The results of this study showed the importance of morning-type, neuroticism , and rigidity as predictors of shift work tolerance. Therefore, in order to select people for shift work systems we recommend to rely on these variables.